Gestos de amor, gestações de lutas: uma etnografia desenhada sobre o movimento mães pela diversidade - Novais, Kaito Campos de (2018)
“Gestos de amor, gestações de lutas” (in English, “Gestures of love, gestations of fights”) is an illustrated ethnography about the Mães pela Diversidade (Mothers for Diversity), association composed by parents and other relatives of lesbian, gays, bisexuals, travestis, transexuals and transgender people (LGBT), that acts in 23 Brazilian states since 2014. Through in-depth interviews, production of a drawing field journal, participant-observation and by the light of theoretical approaches that changed Anthropology after the 60’s – such as feminists, visual and communicational Anthropologies – this dissertation follows the Mothers for Diversity from the state of Goiás and analyses the fights made by the militants throughout the production of the political identity motherhood of LGBT. From field drawings and notes, it discusses how the movement of Mothers incorporates visuals and emotionals estrategies to make these fights. At the end, it concludes that the Mothers for Diversity acionate the motherhood performance in order to built politics inside the LGBT movement and, thus, the association belongs to a wide meshwork of mothers that battles against the violation of human rights commited against their children in Latin America.